Benchmarking of Hi-C tools for scaffolding plant genomes obtained from PacBio HiFi and ONT reads - Obinu, Lia; Trivedi, Urmi; Porceddu, Andrea (Frontiers in Bioinformatics, 2024)
The implementation of Hi-C reads in the de novo genome assembly process allows the ordering of large regions of the genome in scaffolds and the generation of chromosome-level assemblies. Several bioinformatics tools have been developed for genome scaffolding with Hi-C, and each tool has advantages and disadvantages that need to be carefully evaluated before their adoption. We generated two de novo assemblies of Arabidopsis thaliana obtained from the same raw PacBio HiFi and Oxford Nanopore Technologies data. We scaffolded the assemblies implementing Hi-C reads with the scaffolders 3D-DNA, SALSA2, and YaHS, with the aim of identifying the tool providing the most accurate assembly. The scaffolded assemblies were evaluated according to contiguity, completeness, accuracy, and structural correctness. In our analysis, YaHS proved to be the best-performing bioinformatics tool for scaffolding de novo genome assemblies in Arabidopsis thaliana.